Increasing Lysine Content of Waxy Maize through Introgression of Opaque-2 and Opaque-16 Genes Using Molecular Assisted and Biochemical Development - Zhang, Wenlong (Public Library of Science, 2013)
The low lysine content of waxy maize cannot meet the nutritional requirements of humans, livestock, or poultry. In the present study, the high-lysine genes o2 and o16 were backcrossed into wx lines using the maize high-lysine inbreds TAIXI19 (o2o2) and QCL3021 (o16o16) as donors and the waxy maize inbred line QCL5019 (wxwx) as a receptor. In the triple-cross F(1), backcross, and inbred generations, the SSR markers phi027 and phi112 within the wx and o2 genes and the SSR marker umc1121 linked to the o16 gene were used for foreground selection. Background selection of the whole-genome SSR markers was performed for the selected individuals. The grain lysine content was determined using the dye-binding lysine method. The waxiness of the grain was determined with the I(2)-KI staining and dual-wavelength spectrophotometric analysis. The BC(2)F(2) generation included 7 plants of genotype wxwxo2o2O16_, 19 plants of genotype wxwxo16o16O2_, and 3 plants of genotype wxwxo2o2o16o16. In these seeds, the average amylopectin content was 96.67%, 96.87%, and 96.62%, respectively, which is similar to that of QCL5019. The average lysine content was 0.555%, 0.380%, and 0.616%, respectively, representing increases of 75.1%, 19.9%, 94.3%, respectively, over QCL5019. The average genetic background recovery rate of the BC(2)F(3) families was 95.3%, 94.3%, 94.2%, respectively. Among these 3 wxwxo2o2O16O16 families, 4 wxwxo2o2O16o16 families, and 3 wxwxo2o2o16o16 families, the longest imported parent donor fragment was 113.35 cM and the shortest fragment was 11.75 cM. No significant differences in lysine content were found between the BC(2)F(4) seeds and the BC(2)F(3) seeds in these 10 families. This allowed us to increase the lysine content of waxy corn and produce seeds with excellent nutritional characteristics suitable for human consumption, animal feed, and food processing. This may be of significance in the breeding of high-quality corn and in improvement of the nutrition of humans, livestock, and poultry.